Encouragement Motives Student in Watching the Tonight Show D I Net TV - Nahuway, Johana; Waliulu, Yuniar S; Suatrat, Fatima (Yayasan Sembilan Pemuda Indonesia, 2023)
This research was conducted to determine individual motives in enjoying the Tonight Show on Net TV in order to find out different usage patterns in audiences that will have an impact on different levels of satisfaction. Researchers use students as research subjects because students are a very active audience in using mass media, which will be very helpful in identifying their reasons or motives in watching the Tonight Show. Individual motives are seen from four categories of media consumption motives, namely Surveillance Motives, Personal Identity Motives, Interaction Motives and Social Relations and Diversion Motives. Tonight Show is an evening talk show program that provides information and entertainment alongside four hilarious hosts, Desta, Vincent, Hesti Purwadinata and Enzy Storia. The Tonight Show features guest stars from all walks of life who are performed in a relaxed and humorous manner. The approach in this study is quantitative with a descriptive type of research. The method used in this study was a survey method using interview and questionnaire techniques. The respondents in this study were 82 people, which were obtained from sample calculations and distributed in the FISIP campus area of Pattimura University Ambon using Purposive Sampling. The results showed that the diversion motif was greater, the second order was the surveillance motive, the third order was the personal identity motive and the last sequence was the interaction motive and social relationships.